ChemInform Abstract: Silver‐Mediated Methoxycarbonyltetrafluoroethylation of Arenes. Issue 48 (26th November 2013) - Hafner, Andreas; Feuerstein, Thomas J.; Braese, Stefan
Abstract Several conversions of the triazene moiety into different functional groups are presented.